AdpC Is a Prevotella intermedia 17 Leucine-Rich Repeat Internalin-Like Protein - Iyer, Divya (American Society for Microbiology (ASM), 2010)
The oral bacterium Prevotella intermedia attaches to and invades gingival epithelial cells, fibroblasts, and endothelial cells. Several genes encoding proteins that mediate both the adhesion and invasion processes are carried on the genome of this bacterium. Here, we characterized one such protein, AdpC, belonging to the leucine-rich repeat (LRR) protein family. Bioinformatics analysis revealed that this protein shares similarity with the Treponema pallidum LRR (LRR(TP)) family of proteins and contains six LRRs. Despite the absence of a signal peptide, this protein is localized on the bacterial outer membrane, indicating that it is transported through an atypical secretion mechanism. The recombinant form of this protein (rAdpC) was shown to bind fibrinogen. In addition, the heterologous host strain Escherichia coli BL21 expressing rAdpC (V2846) invaded fibroblast NIH 3T3 cells at a 40-fold-higher frequency than control E. coli BL21 cells expressing a sham P. intermedia 17 protein. Although similar results were obtained by using human umbilical vein endothelial cells (HUVECs), only a 3-fold-increased invasion of V2846 into oral epithelial HN4 cells was observed. Thus, AdpC-mediated invasion is cell specific. This work demonstrated that AdpC is an important invasin protein of P. intermedia 17.